Analysis of Platelet Shape Al2O3 and TiO2 on Heat Generative Hydromagnetic Nanofluids for the Base Fluid C2H6O2 in a Vertical Channel of Porous Medium - HAZARIKA, Silpi; AHMED, Sahin; CHAMKHA, Ali J. (Walailak Journal of Science and Technology (WJST), 2021)
An analytical investigation is performed on the unsteady hydromagnetic flow of nanoparticles Al2O3 and TiO2 in the EG base fluid through a saturated porous medium bounded by two vertical surfaces with heat generation and no-slip boundary conditions. The physics of initial and boundary conditions is designated with the flow model’s non-linear partial differential equations. The analytical expressions of nanofluid velocity and temperature with the channel are derived, and Matlab Codes are used to plot the significant results for physical variables. From the physical point of view for nanofluid velocity and temperature results, the base fluid C2H6O2 has a higher viscosity and thermal conductivity than that of water. Physically, the platelet shape Al2O3 nanofluid has the highest velocity than TiO2 nanofluid. It is found that the velocity of nanofluid enhanced the porosity and nanoparticles volume fraction for Al2O3 - EG and TiO2 - EG base nanofluids. However, this trend is reversed for the effects of heat generation. Obtained results indicate that an increase in nanoparticles volume fraction raises the skin friction near the surface, but profiles gradually become linear, due to less frictional effects of nanoparticles. Moreover, due to higher values of nanoparticles volume fraction, the thermal conductivity is raised, and thus the thickness of the thermal boundary layer is declined. The results show that the method provides excellent approximations to the analytical solution of nonlinear system with high accuracy. Metal oxide nanoparticles have wide applications in various fields due to their small sizes, such as the pharmaceutical industry and biomedical engineering. HIGHLIGHTS Impact of platelet shape Al2O3 and TiO2 for base fluid C2H6O2 is studied In Couette and Poiseuille flow, nanoparticles play a vital role to enhance the heat transfer The infinite series solution has been used for solving the non-linear PDE’s The uses of Al2O3 and TiO2 in significant heat transfer applications is overviewed The physiochemical and structural features of metal oxide nanoparticles have diverse biomedical applications GRAPHICAL ABSTRACT